Soft Skills of Software Developers: Exploring the Pandemic's Impact of COVID-19 - Silva, Rayane Moraes da; Vilela, Ricardo Ferreira; Valle, Pedro Henrique Dias (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Context: The software industry has invested efforts to identify and understand the soft skills required for good software developers in recent years. Problem: However, with the face of the COVID-19 pandemic, it was observed that the soft skills of developers suffer impacts, mainly on the mental health and well-being of people and their families. Objective: In this context, this work aims to obtain an overview of the impacts that the soft skills of software developers suffered when facing the COVID-19 pandemic. Method: For this, we conducted a survey with software developers to obtain an overview of this scenario. Results: we received 101 responses from different states in Brazil, in which software developers indicated which soft skills they believe were positively, negatively impacted or those that were not affected. In addition, respondents also indicated which soft skills they believe were acquired after this event. Conclusion: From the results, we observed that most developers believe that their skills were positively impacted after the COVID-19 pandemic. Among them, the following stand out: flexibility, empathy, adaptability, fast learning, and desire to learn.